ANALISIS DROP TEGANGAN PADA JARINGAN TEGANGAN MENENGAH DENGAN MENGGUNAKAN SIMULASI PROGRAM ETAP - Redaksi Tim Jurnal (Energi & Kelistrikan, 2018)
Distribution system is very important in the distribution of electric power to the load. Therefore, a good and efficient distribution system is needed. The underlying cause of poor electric power distribution system is the amount of voltage drop values in the existing system. In the electric power distribution, 20 kV medium-voltage and 380/220V low voltage networks are used. The distribution system of Gandum Feeder in Angke Substation uses medium-voltage network with Underground Cable channel. They are used because of the towering buildings and the dense population in the area. It is known that the longest the channel and the load current are, the greater the voltage drop. From the result of the voltage drop calculation of Feeder Gandum in Angke Substation, which uses manual calculation and ETAP 12.6.0 program, it showed a slight difference in the result. The result of the voltage drop obtained from manual calculation showed that the percentage value of voltage is 1,94%, while the result obtained from ETAP 12.6.0 program showed that the percentage value is 2,01% These results are still in the PLN standard, because it has not exceeded the specified standard that is -10% of its nominal voltage.